Perlindungan Hukum bagi Tenaga Medis dan Tenaga Kesehatan dalam Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan - Prayuti, Yuyut; Kusumah, Yuda; Abidin, Zaenal (Legal Standing : Jurnal Ilmu Hukum, 2025)
The current position of patients, which can be said to be equal to healthcare professionals, makes healthcare providers unable to ignore regulations that may conflict with criminal, civil, and administrative law. In cases of malpractice, patients can directly report and demand accountability. The problem in this research is that healthcare providers, healthcare professionals, and medical personnel can face legal consequences if proven to have provided healthcare services that do not comply with existing Professional Standards and Standard Operating Procedures. This research uses a normative juridical research method, relying on primary data sources in the form of laws and regulations related to the problem, namely Law No. 17 of 2023 concerning Health, Law No. 36 of 2014 concerning Health Workers, and Law No. 44 of 2009 concerning Hospitals. Secondary data sources include books, professional codes of ethics, law journals, theses, and dissertations that provide guidance and explanations regarding primary data sources. In Law Number 17 of 2023 concerning Health, Article 273 provides legal protection for healthcare professionals and medical personnel who perform medical actions in healthcare services as long as they comply with professional standards, professional service standards, Standards operational procedure, and professional ethics. It also seeks to resolve disputes resulting from negligence outside of court. This research is limited to a normative legal analysis, focusing on laws and regulations without empirical validation from case studies or direct interviews with affected professionals and patients. The study also does not explore international comparative law, which may provide broader insights into malpractice accountability.